Impact of Cryopreservation on Viability, Phenotype, and Functionality of Porcine PBMC - Li, Yanli; Mateu, Enric; Díaz, Ivan (Frontiers in Immunology, 2021)
The use of frozen peripheral blood mononuclear cells (PBMC) is common in immunological studies. The impact of freezing PBMC has been assessed using human and mice cells, but little information is available regarding domestic animals. In the present study, the phenotype and functionality of frozen porcine PBMC were examined. In a preliminary experiment, three freezing media: fetal bovine serum plus 10% dimethyl sulfoxide, PSC cryopreservation kit, and Cryostor CS10, were compared regarding the preservation of cell viability and the response of PBMC to mitogens after thawing. After being stored one month in liquid nitrogen, cell viability was above 89% for all freezing media. The ELISPOT IFN-gamma (IFN-γ) results in response to PHA and of IgG ELISPOT in response to R848+IL-2 were similar to those obtained using fresh PBMC. In the second set of experiments, PBMC were obtained from five pigs vaccinated against porcine reproductive and respiratory syndrome virus (PRRSV) and then frozen using Cryostor CS10. Recovered cells were phenotyped by flow cytometry using anti-CD3, CD4, CD8, and CD21 antibodies and were used to assess the PRRSV-specific responses in a proliferation experiment, an IFN-γ ELISPOT, and an IgG ELISPOT, and compared to the results obtained with fresh cells. The antigen-specific responses of frozen cells were significantly (p<0.05) impaired in the proliferation assay, particularly for CD4/CD8 double-positive T-cells and for CD21+ cells. Freezing resulted in decreased proliferation when Con A, but not PHA, was used. In ELISPOT, cryopreservation resulted in a decreased frequency of IFN-γ-secreting cells in response to PRRSV (p<0.05) but the response to PHA was not affected. No differences were observed in the IgG ELISPOT after polyclonal activation. Taken together, cryopreservation of porcine PBMC had a significant impact on the magnitude of recall antigen responses and therefore, it may affect the response of effector/memory cells but seems not to have a major impact on naïve T-cells. These results may help to the better use of pig frozen PBMC, and to the interpretation of the results obtained from them.